PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN SUMUR WELUT III SURABAYA - Ana Fitriana; Bahauddin Azmy; Via Yustitia (Badan Penerbit STIEPARI Press, 2022)
This studies is influenced with the low results of science studying of class students 5 elementary school. The low science learning outcomes are affected by many factors. This factors include the studying environment in the form of strategies created by the teacher to optimize the potential of students in studying science. The aim of this studies is to determine the impact of problem based learning on science studying results for fifth grade students at Sumur Welut III Public Elementary School Surabaya. This learn uses a quantitative experimental method with a quasi-experimental design using a posttest-only control group design. The population of this study were students of class A and B at Sumur Welut III Public Elementary School Surabaya with a total of 46 children. The data collection method used is a testing. Giving the test in question is a posttest which is carried out after learning. The data analysis techniques used are the normality test, the homogeneity test, and the t-test. Based on the results of the survey, it was shown that the application of problem based learning influenced the learning outcomes of the fifth grade students in Sumur Welut III Public Elementary School Surabaya. This is indicated by the average difference in the scientific learning results between the experimental and control classes.